Characteristics of Ebola Virus Disease Survivor Blood and Semen in Liberia: Serology and Reverse Transcription Polymerase Chain Reaction (RT-PCR). (7th September 2020) - Kofman, Aaron; Linderman, Susanne; Su, Kaihong; Purpura, Lawrence J; Ervin, Elizabeth; Brown, Shelley; Morales-Betoulle, Maria; Graziano, James; Cannon, Deborah L; Klena, John D; Desamu-Thorpe, Rodel; Fankhauser, John; et al.
Abstract: Introduction: Ebola virus (EBOV), species Zaire ebolavirus, may persist in the semen of male survivors of Ebola virus disease (EVD). We conducted a study of male survivors of the 2014–2016 EVD outbreak in Liberia and evaluated their immune responses to EBOV. We report here findings from the serologic testing of blood for EBOV-specific antibodies, molecular testing for EBOV in blood and semen, and serologic testing of peripheral blood mononuclear cells (PBMCs) in a subset of study participants. Methods: We tested for EBOV RNA in blood by quantitative reverse transcription polymerase chain reaction (qRT-PCR), and for anti-EBOV-specific immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies by enzyme-linked immunosorbent assay (ELISA) for 126 study participants. We performed PBMC analysis on a subgroup of 26 IgG-negative participants. Results: All 126 participants tested negative for EBOV RNA in blood by qRT-PCR. The blood of 26 participants tested negative for EBOV-specific IgG antibodies by ELISA. PBMCs were collected from 23/26 EBOV IgG-negative participants. Of these, 1/23 participants had PBMCs that produced anti-EBOV-specific IgG antibodies upon stimulation with EBOV-specific glycoprotein (GP) and nucleoprotein (NP) antigens. Conclusions: The blood of EVD survivors, collected when they did not have symptoms meeting the case definition for acute or relapsed EVD, is unlikely to pose a risk for EBOV transmission. We identified 1 IgM/IgG negative participant who had PBMCs that produced anti-EBOV-specific antibodies upon stimulation. Immunogenicity following acute EBOV infection may exist along a spectrum, and absence of antibody response should not be exclusionary in determining an individual's status as a survivor of EVD. Abstract : In our study of Ebola Virus Disease (EVD) survivors from Liberia following the 2014-2016 EVD outbreak, we found that none had detectable Ebola Virus (EBOV) polymerase chain reaction in blood. One immunoglobulin M/immunoglobulin G negative participant had anti-EBOV-specific peripheral blood mononuclear cell activity.